Physical modelling of a cantilever wall. Issue 2 (June 2004) - Gaudin, Christophe; Garnier, Jacques; Thorel, Luc
Abstract : Centrifuge modelling is henceforth a recognized experimental technique. Its use for study of retaining wall was until now slowed down by the necessity to carry out in-flight excavation in order to model correctly the stress history in the structure. A new experimental study was then carried out in the Laboratoire Central des Ponts et Chaussées to validate the use of a new robot to simulate excavation process in front of retaining structures and to perform complementary operation related to the behaviour of the wall. For this purpose, the behaviour of a 10 m high cantilever wall, embedded in dry Fontainebleau sand, was studied as well as the interaction between the cantilever wall and a strip footing placed close to the wall. Both experimental devices and procedure are presented in details. The data recording device gives access to both displacements of the wall and the strip footing and to the bending moments in the wall. Experimental results are presented and commented and show the validity of the procedure and the potentiality of this device to study more complex or realistic problems involving retaining structures.